Regulation of PaRBOH1-mediated ROS production in Norway spruce by Ca2+ binding and phosphorylation - Nickolov, Kaloian; Gauthier, Adrien; Hashimoto, Kenji; Laitinen, Teresa; Väisänen, Enni; Paasela, Tanja; Soliymani, Rabah; Kurusu, Takamitsu; Himanen, Kristiina; Blokhina, Olga; Fagerstedt, Kurt V.; Jokipii-Lukkari, Soile; et al. (Frontiers in Plant Science, 2022)
Plant respiratory burst oxidase homologs (RBOHs) are plasma membrane-localized NADPH oxidases that generate superoxide anion radicals, which then dismutate to H2O2, into the apoplast using cytoplasmic NADPH as an electron donor. PaRBOH1 is the most highly expressed RBOH gene in developing xylem as well as in a lignin-forming cell culture of Norway spruce (Picea abies L. Karst.). Since no previous information about regulation of gymnosperm RBOHs exist, our aim was to resolve how PaRBOH1 is regulated with a focus on phosphorylation. The N-terminal part of PaRBOH1 was found to contain several putative phosphorylation sites and a four-times repeated motif with similarities to the Botrytis-induced kinase 1 target site in Arabidopsis AtRBOHD. Phosphorylation was indicated for six of the sites in in vitro kinase assays using 15 amino-acid-long peptides for each of the predicted phosphotarget site in the presence of protein extracts of developing xylem. Serine and threonine residues showing positive response in the peptide assays were individually mutated to alanine (kinase-inactive) or to aspartate (phosphomimic), and the wild type PaRBOH1 and the mutated constructs transfected to human kidney embryogenic (HEK293T) cells with a low endogenous level of extracellular ROS production. ROS-producing assays with HEK cells showed that Ca2+ and phosphorylation synergistically activate the enzyme and identified several serine and threonine residues that are likely to be phosphorylated including a novel phosphorylation site not characterized in other plant species. These were further investigated with a phosphoproteomic study. Results of Norway spruce, the first gymnosperm species studied in relation to RBOH regulation, show that regulation of RBOH activity is conserved among seed plants.